Follow the leader: How expert ratings mediate consumer assessments of hedonic quality - D. Priilaid; J. Feinberg; O. Carter; G. Ross (South African Journal of Business Management, 2009)
Within the context of sighted wine appreciation, previous studies indicate that extrinsic cues like price and area-of-origin have a marked effect on the sighted ratings proffered by tasting experts. While these expert ratings are widely employed by the wine media as proxies of genuine quality, it remains uncertain whether such expert ratings, in turn, serve to influence the public in their own sighted assessments of wine quality. To determine the influence of the expert rating cue in the public's sighted appreciation of wine, a tasting-room experiment was held in which 32 subjects assessed seven wines first blind and then sighted. During the sighted tasting the only (additional) cue-information made available was the expert rating conferred by the South African annual wine-guide known as John Platter. An interrogation of the resultant database of 224 paired blind and sighted wine assessments reveals the extent to which the expert rating cue consistently mediates the sighted appreciation of wine, this particularly within the younger, less experienced demographic. An examination of the meta-model's driving coefficients suggests that in explaining sighted quality, expert ratings appear to operate at five times the strength of the original intrinsic (blind) assessment. For marketers, this finding suggests (1) that the promotion of this extrinsic cue be targeted more specifically at wine "novices", and (2) that this narrowing of marketing focus implies a more judicious and effective employment of media budgets.
Keywords: 650